Assessing the Role of the Oil Market in Rising Food Prices: Strategic Implications for Food Security in Gulf Cooperation Council Countries - Ebadi, Esmaeil; Balcilar, Mehmet; Are, Wasiu (International Journal of Energy Economics and Policy, 2024)
This study examines the relationship between oil prices and food prices, with a focus on key agricultural commodities in the United States, including corn, soybeans, wheat flour, meat, and milk. Using a regime-switching cointegration approach, the research investigates both the long-term and short- term dynamics of oil’s impact on food prices. The findings indicate that oil prices exert an asymmetric influence on the food market. While oil prices play a relatively limited role in determining certain production costs, particularly for meat, compared to other economic factors, they nonetheless hold strong predictive power for food price forecasts. Notably, any short-term disequilibria in prices prompt a rapid adjustment back to equilibrium, contributing to market stability. The study suggests that Gulf Cooperation Council (GCC) countries, which rely heavily on food imports, can leverage their energy resources to alleviate the inflationary pressures in food markets resulting from global demand increases. A key long-term strategy involves investing in energy-intensive agricultural technologies, such as desalination for water supply and controlled-environment agriculture (e.g., greenhouses), underscoring the need for strategic foresight and comprehensive planning in agricultural investments.